Systematic Literature Review Pengaruh Pendidikan Kewirausahaan dalam Meningkatkan Minat Berwirausaha Siswa di Sekolah Menengah Kejuruan - Enjang Suhaedin; Ganefri; Asmar Yulastri (SAFE-Network, 2023)
Entrepreneurship refers to the process or individual actions of creating, developing, and managing a new venture or business with the aim of achieving financial gain. Understanding of entrepreneurship includes business concepts, business development strategies, operational management, finance, marketing, as well as leadership and communication skills. This research is a literature study which aims to identify and explore the influence of knowledge on Vocational High School (SMK) students' interest in entrepreneurship, using a qualitative descriptive approach to seven scientific articles. The research method used is Systematic Literature Review (SLR) with the steps, namely compiling a Research Question (RQ), searching for relevant literature, conducting a review, analyzing the findings. The aim of this study is to determine the influence of entrepreneurship education on vocational high school students' interest in entrepreneurship. The research results show that entrepreneurial knowledge has a positive and significant influence on vocational school students' interest in entrepreneurship.